Bacterial and Fungal Coinfections in COVID-19 Inpatients at a Tertiary Hospital in Surabaya, Indonesia, from November 2020 to February 2022 - Shabira, Naura Ghina; Widodo, Agung Dwi Wahyu; Rusli, Musofa (Universitas Airlangga, 2025)
Introduction: After the first discovery of coronavirus disease 2019 (COVID-19) in 2020, the rapid increase of cases beyond China prompted the declaration of a pandemic. Elevated rates of bacterial-fungal coinfection were observed in hospitalized COVID-19 patients. This study aimed to determine the profiles of bacterial and fungal coinfections in COVID-19 patients diagnosed between November 2020 and February 2022 at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Methods: This retrospective descriptive study obtained data from medical records and used total sampling to assemble 278 COVID-19 patients who met the inclusion criteria. The evaluated variables were subject characteristics, including age, sex, comorbidities, length of stay, ventilator use, bacterial coinfections, fungal coinfections, and bacterial-fungal coinfections. Results: The age group of 55–64 years (26.9%) was predominant among the patients, with males (55.4%) outnumbering females. Hypertension was the most prevalent comorbidity (15.8%). The patients were mostly hospitalized for over ten days (66.2%). Eleven patients (4%) were admitted to the intensive care unit, and five patients (1.8%) required mechanical ventilation. The bacterial coinfections were primarily caused by Streptococcus viridans (56.6%), found in 145 sputum specimens, followed by Klebsiella pneumoniae (23.4%). The predominant isolates in the bacterial-fungal coinfections were Streptococcus viridans and Candida albicans (24.8%), identified in 125 sputum specimens, followed by Klebsiella pneumoniae and Candida albicans (18.4%). Conclusion: COVID-19 patients with bacterial-fungal coinfections present certain characteristics, including being male, middle-aged, hypertensive, and hospitalized beyond ten days. Streptococcus viridans, Klebsiella pneumoniae, and Candida albicans are common etiologies in bacterial-fungal coinfections. Highlights: 1. This study overviews the distribution of patients and causative pathogens associated with bacterial, fungal, and bacterial-fungal coinfections, which have escalated with the rapid rise of coronavirus disease 2019 (COVID-19) hospitalization. 2. Data on the causative pathogens of bacterial-fungal coinfection in COVID-19 patients can be considered in the development of guidelines for empirical therapy in clinical practice.